ONE DIMENSIONAL SIMULATION OF DC BIASED ARGON PLASMA USING COMSOL MULTIPHYSICS - Dionysius Joseph Djoko Herry Santjojo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
The character of a argon plasma in a DC biased reactor was simulated using 1-dimensional model. The model and simulation was carried out using COMSOL multiphysics software. Results of the simulation show that the model and can be used to predict the character and state of the Ar plasma such as distribution of electron density and Ar+ ion, electron temperature, and electric potential in the plasma space. Furthermore, the model predicts that the argon plasma is formed near the cathode (r<0.5 cm) at the end of the simulation. And, the higher the pressure the higher the plasma density produced at pressures less than 100 Pa.